Oxygen micro profiles of multi-corer sediment core HE595_48-3 - Müller, Daniel; Holtappels, Moritz; Liu, Bo; Dohrmann, Ingrid; Bethke, Denise; Kasten, Sabine (In: Müller, D et al. (2024): Oxygen micro profiles of multi-corer sediment cores taken during RV Heincke cruise HE595 in the Helgoland Mud Area, SE German Bight [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.970325, 2024)
This dataset includes onboard measurements of 100 μm vertical resolution oxygen micro-profiles from multi-corer cores retrieved during RV Heincke expeditions HE595 in 2022. Three to five measurements for each core were performed using micro-optodes with a tip diameter of 50 µm (OXR50, High Speed, Pyroscience). The samples were collected in the framework of the Project APOC (Anthropogenic impacts on particulate organic carbon cycling in the North Sea).
Keywords: Geochemical data; German Bight; North Sea; Oxygen; profiles; sediment